Cytotoxic and Genotoxic Effects of Acephate on Human Sperm - M. A. Thamali Dhanushka; L. Dinithi. C. Peiris (Journal of Toxicology)
Extensive use of organophosphorus pesticides (OPs) could alter semen quality and sperm DNA at different stages of spermatogenesis. Acephate is a highly toxic extensively used OP and, therefore, we aimed to evaluate the effects of acephate on human semen quality and sperm DNA integrity. Sperm collected from healthy males were exposed to 0, 50, 100, and 200 μg/mL of acephate and incubated for 1 h, 2 h, and 3 h. Subsequently, sperm motility, vitality, functional integrity of plasma membrane, sperm capacitation, and DNA damage were examined. Result showed a significant decline of the motility at 100 μg/mL after 3 h and with 200 μg/mL after 1 h, 2 h, and 3 h. Viability was significantly reduced at 200 μg/mL after 2 h and 3 h. Functional integrity was significantly affected at 100 μg/mL after 3h and in 200 μg/mL dose after 2 h and 3h. Similarly, sperm capacitation was significantly affected at 200 μg/mL after 1 h, 2 h, and 3 h and at 100 μg/mL at 3 h. DNA damage was significantly increased only in 200 μg/mL dose after 3 h. The study suggests that exposure to acephate may result in alterations of sperm structure and function thus contributing towards deteriorating in human semen quality triggering infertility.